Lenalidomide normalizes tumor vessels in colorectal cancer improving chemotherapy activity. Issue 1 (December 2016) - Leuci, V.; Maione, F.; Rotolo, R.; Giraudo, E.; Sassi, F.; Migliardi, G.; Todorovic, M.; Gammaitoni, L.; Mesiano, G.; Giraudo, L.; Luraghi, P.; Leone, F.; et al.
Abstract Background Angiogenesis inhibition is a promising approach for treating metastatic colorectal cancer (mCRC). Recent evidences support the seemingly counterintuitive ability of certain antiangiogenic drugs to promote normalization of residual tumor vessels with important clinical implications. Lenalidomide is an oral drug with immune-modulatory and anti-angiogenic activity against selected hematologic malignancies but as yet little is known regarding its effectiveness for solid tumors. The aim of this study was to determine whether lenalidomide can normalize colorectal cancer neo-vessels in vivo, thus reducing tumor hypoxia and improving the benefit of chemotherapy. Methods We set up a tumorgraft model with NOD/SCID mice implanted with a patient-derived colorectal cancer liver metastasis. The mice were treated with oral lenalidomide (50 mg/Kg/day for 28 days), intraperitoneal 5-fluorouracil (5FU) (20 mg/Kg twice weekly for 3 weeks), combination (combo) of lenalidomide and 5FU or irrelevant vehicle. We assessed tumor vessel density (CD146), pericyte coverage (NG2; alphaSMA), in vivo perfusion capability of residual vessels (lectin distribution essay), hypoxic areas (HP2-100 Hypoxyprobe) and antitumor activity in vivo and in vitro. Results Treatment with lenalidomide reduced tumor vessel density (p = 0.0001) and enhanced mature pericyte coverage of residual vessels (p = 0.002). Perfusion capability of tumor vessels was enhanced in mice treated with lenalidomide compared to controls (p = 0.004). Accordingly, lenalidomide reduced hypoxic tumor areas (p = 0.002) and enhanced the antitumor activity of 5FU in vivo. The combo treatment delayed tumor growth (p = 0.01) and significantly reduced the Ki67 index (p = 0.0002). Lenalidomide alone did not demonstrate antitumor activity compared to untreated controls in vivo or against 4 different mCRC cell lines in vitro. Conclusions We provide the first evidence of tumor vessel normalization and hypoxia reduction induced by lenalidomide in mCRC in vivo. This effect, seemingly counterintuitive for an antiangiogenic compound, translates into indirect antitumor activity thus enhancing the therapeutic index of chemotherapy. Our findings suggest that further research should be carried out on synergism between lenalidomide and conventional therapies for treating solid tumors that might benefit from tumor vasculature normalization.